The effectiveness of L-PRF in the treatment of schneiderian membrane large perforations: Long-term follow-up of a case series - De Almeida Malzoni, Carolina Mendonça [UNESP] (2021)
The perforation of the Schneiderian membrane (SM) is a common surgical complication during the sinus floor augmentation (SFA) procedure. Different approaches have been proposed to completely closer the SM perforation and to avoid graft contamination or migration and postoperative sinus infection. In this context, the leukocyte and platelet-rich fibrin (L-PRF) membranes have been proposed for SM perforation treatment because of their natural adhesive property and resistance. Thus, this case series aims to evaluate the effectiveness of L-PRF in the treatment of SM large perforations during SFA. A total of 9 SM perforations were treated in this case series. The L-PRF membranes were interposed on the perforated SM until the rupture could not be visualized. The maxillary sinus cavities were filled with deproteinized bovine mineral bone (Bio-oss, Geistlich, Switzerland), and a collagen membrane was positioned to cover the lateral access window. After 8 months, 13 implants were placed, achieving satisfactory primary stability. The osseointegration of all implants and absence of infection signs/mucus in the maxillary sinus were observed in cone beam computed tomography or panoramic radiography qualitative analysis after 3-5 years of follow-up. It can be concluded that the use of L-PRF can be considered a viable alternative for the repair of large SM perforations.